Pengaruh Penggunaan Model Pembelajaran Berbasis Masalah Terhadap Keterampilan Menulis Karangan Eksposisi - Uli Wahyuni (Universitas Batanghari Jambi, 2021)
This study aims to find out the influence of problem-based learning models on writing skills by exposition of grade X students of SMA Negeri 1 Muara Bungo. This type of research is quantitative research using experimental methods. The type of experiment in this study is quasi experiment. The population of this study is grade X students of SMA Negeri 1 Muara Bungo. Sampling is done in simple random sampling. This research instrument is in the form of questionnaires and performance tests. This research data is in the form of test scores of work performance skills writing essays exposition. The data was analyzed using liliefors normality test, variance homogeneity test, hypothesis test using t test, and two-way anova test. Based on the results of data analysis and discussion found two test results of writing skills written by exposition of students who were taught using a problem-based learning model better than students who were taught using conventional models. One, this hypothesis is accepted because th > tt with α=0.05. So it can be said that there is a significant influence of a problem-based learning model on the writing skills of exposition essays. Two, There is no interaction between problem-based learning models of exposition writing skills. This hypothesis is accepted because fh < ft with α=0.05. So it can be said that between problem-based learning models are not interrelated in influencing the writing skills of exposition essays.